CREATIVE PERSON AND CREATIVE PROCESS (Author: Frank Barron) - Bews, Mary (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1972)
Frank Barron, CREATIVE PERSON AND CREATIVE PROCESS. New York: Holt, Rinehart and Winston, 1969. 212 pp. - $3.95.